A Systematic Analysis Reveals the Prognostic and Immunological Role of Reptin/RUVBL2 in Human Tumors - Su, Xiaoru; Zheng, Gaoming; Gui, Zhifang; Yang, Xiao; Zhang, Lahong; Pan, Feng (Frontiers in Genetics, 2022)
Reptin/RUVBL2 is involved in the remodeling of chromatin, DNA damage repair, and regulation of the cell cycle, all of which help to play essential roles in cancer. However, relevant pan-cancer analysis of Reptin is lacking. This study first investigated the potential oncogenic roles of Reptin and revealed a relationship between Reptin with clinicopathological characteristics and immune infiltration based on big data. Here, we showed that Reptin is overexpressed in many cancers. A significant association exists between the expression of Reptin and the prognosis of cancer cases. Reptin had a meaningful interaction with the immune infiltration of CD4+ Th1 cells and immune modulator genes in multiple cancer types. And negative correlation exists between Reptin and cancer-associated fibroblasts in BRCA, PRAD, TGCT, and THYM. A significant negative association exists between Reptin and regulatory T cells in TGCT and THCA. Moreover, Reptin is significantly associated with genomic heterogeneity, DNA mismatch repair genes, methyltransferase, and RNA modification genes in specific cancer types. Spliceosome, Hippo signaling pathway, DNA replication pathway, and acetyltransferase activity-associated functions were observed in the effect of Reptin on the tumor. This systematic analysis highlights Reptin as a vital cancer regulator among numerous genes and probably assists future mechanism research and tumor immunotherapy targeting Reptin.